Research of New Technologies That Allow Selecting Tolador Seeds - Muhammadjonova, I.; Madumarov, I. D. (International Journal of Development and Public Policy, 2021)
The aim of the research work is to increase the yield of cotton fiber by improving the processing technology of germinated seeds, to improve the quality indicators of seeds and lint. In order achieve this goal; a mesh surface device was created to sort the seeds into fractions. Sorting technology was developed on this device and operating modes were determined. In addition, the law of surface distribution of the fractions separated from the cotton stream moving along the surface of the net was determined, and based on the results of practical and theoretical research, a mode of sorting of cotton seeds was developed.